1980
DOI: 10.1007/bf00964226
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in brain protein synthesis in the rat

Abstract: Brain protein synthesis was studied in vivo, in brain slices, and in cell-free systems in rats aged 1, 16, and 24 months. We observed a highly significant reduction in amino acid incorporation with advancing age. This reduction was observed in vivo, in slices, in postmitochondrial supernatant, microsomes, and membrane-bound polysomes. Free heavy polysomes showed no age-dependent decline but formed a smaller proportion of total ribosomes in older animals. These studies suggest that in the rat brain protein synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Prior to this time, the experimental methods did not consider specific activity of the precursor pool (reviewed by Richardson and Birchenall-Sparks, 1983), which resulted in highly variable outcomes across studies. Using improved methodology, several groups found that levels of brain protein synthesis increase during development in the rodent, reaching maximum levels sometime during the first 6 months of age, and then decline thereafter (Dwyer et al, 1980; Ekstrom et al, 1980; Fando et al, 1980; Ingvar et al, 1985; Smith et al, 1995; but see Filion and Laughrea, 1985; reviewed by Richardson, 1981; Richardson and Birchenall-Sparks, 1983; Richardson et al, 1983). A similar pattern was observed in the white leghorn chicken (Yang et al, 1977).…”
Section: Transcription and Translation In The Aging Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this time, the experimental methods did not consider specific activity of the precursor pool (reviewed by Richardson and Birchenall-Sparks, 1983), which resulted in highly variable outcomes across studies. Using improved methodology, several groups found that levels of brain protein synthesis increase during development in the rodent, reaching maximum levels sometime during the first 6 months of age, and then decline thereafter (Dwyer et al, 1980; Ekstrom et al, 1980; Fando et al, 1980; Ingvar et al, 1985; Smith et al, 1995; but see Filion and Laughrea, 1985; reviewed by Richardson, 1981; Richardson and Birchenall-Sparks, 1983; Richardson et al, 1983). A similar pattern was observed in the white leghorn chicken (Yang et al, 1977).…”
Section: Transcription and Translation In The Aging Brainmentioning
confidence: 99%
“…A similar pattern was observed in the white leghorn chicken (Yang et al, 1977). There is some disagreement pertaining to the exact time course of the decline, with some finding a greater rate of decline in translation during adulthood (Ekstrom et al, 1980; Fando et al, 1980; Ingvar et al, 1985; Smith et al, 1995), and others finding the greatest rate of decline during senescence (Dwyer et al, 1980). Similarly, although protein synthesis decline has been observed in many other types of tissues and cells (e.g., liver, kidney, muscle), the time courses and rates of decline vary (reviewed by Webster, 1985).…”
Section: Transcription and Translation In The Aging Brainmentioning
confidence: 99%
“…A 20% decrease of mean CPSR was measured due to ageing in the brain of 11 to 26 month-old Wistar rats. This impairment (-18% to -37%) was conf i e d by measurements of the brain metabolism of L-leucine in rat (Ekstrom et al, 1980;Fando et al, 1980;Ingvar et al, 1985) based on different models. Our results, the absolute ROI CPSR values given in table I for the two control groups, were also confirmed by other similar studies with [35S]-L-methionine (Lestage et Williams et al, 1994).…”
Section: Effect Of Aging On Cpsrmentioning
confidence: 80%
“…In contrast, hepatic tissue basal levels of NAT-1 decreased with age. It is not known whether these changes would contribute to the age-related decrease in cerebral protein synthesis (28,29) or the age-related increase in hepatic protein synthesis (30,31).…”
Section: Resultsmentioning
confidence: 99%